Communal bonding seen during Narali Purnima - Mumbai Archive Project Team (Jio Institute, 2024)
Narali Purnima promotes communal bonding by bringing families and neighbours together to partake in the rituals and celebrations. The festival remains a vital part of the Koli identity, celebrating their way of life and ensuring the continuity of their traditions for future generations.